1990
DOI: 10.1021/bi00478a026
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group proteins 1 and 2 function as general class II transcription factors

Abstract: High mobility group (HMG) proteins 1 and 2 are thought to be associated with chromatin enriched in active gene sequences, to stimulate endogenous transcription of class II and III genes using HMG-depleted nuclei, and to bind specific DNA sequences upstream of the coding regions of trout HMG-T and human beta-globin genes. In testing the possibility that these proteins may act as general transcription factors, the run-off transcription of trout protamine, human beta-globin, adenovirus 2 major late promoter, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
0
2

Year Published

1991
1991
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 48 publications
3
66
0
2
Order By: Relevance
“…They bind doubleand single-stranded DNA with no apparent sequence specificity, although they bind with markedly higher affinity to cruciform structures (Wright and Dixon 1988;Bianchi et al 1989) and cis-platin-modified DNA (Pil and Lippard 1992). The exact functions of HMG1 and HMG2 are not yet known, although stimulatory effects of HMG1 and HMG2 on transcription (Stoute and Marzluff 1982;Tremethick andMolloy 1986,1988;Singh and Dixon 1990), DNA replication (Alexandrova et al 1984;Alexandrova and Behchev 1988), and nucleosome assembly (Bonne-Andrea et al 1984) have been reported. Our results with the Hin site-specific recombination reaction suggest that one specific function of HMG1 and HMG2 is to promote assembly of higher order nucleoprotein complexes, a feature that may be common to each of the processes cited above.…”
Section: Discussionmentioning
confidence: 99%
“…They bind doubleand single-stranded DNA with no apparent sequence specificity, although they bind with markedly higher affinity to cruciform structures (Wright and Dixon 1988;Bianchi et al 1989) and cis-platin-modified DNA (Pil and Lippard 1992). The exact functions of HMG1 and HMG2 are not yet known, although stimulatory effects of HMG1 and HMG2 on transcription (Stoute and Marzluff 1982;Tremethick andMolloy 1986,1988;Singh and Dixon 1990), DNA replication (Alexandrova et al 1984;Alexandrova and Behchev 1988), and nucleosome assembly (Bonne-Andrea et al 1984) have been reported. Our results with the Hin site-specific recombination reaction suggest that one specific function of HMG1 and HMG2 is to promote assembly of higher order nucleoprotein complexes, a feature that may be common to each of the processes cited above.…”
Section: Discussionmentioning
confidence: 99%
“…These HMG proteins constitute an important class of nonhistone chromosomal proteins of eukaryotes (reviewed in references 35 and 77). Although their cellular function remains unknown, they have been implicated in nuclear processes such as transcription (71,76), DNA replication (32), and chromatin assembly (9). Consistent with a role in chromatin structure, it was shown that the SPT2/SIN1 protein is concentrated in the nucleus and that an increase in chromosome instability is observed in sinl mutants (42).…”
Section: Materuils and Methodsmentioning
confidence: 98%
“…) and plays a role in nucleosome assembly/disassembly (Bonne-Andrea et al, 1984;Waga et al, 1989), the regulation of transcription (Watt & Molloy, 1988;Singh & Dixon, 1990), binding to cruciform structures of DNA (Bianchi et al, 1989) and in chromatin (Scovell et al, 1987), and in the process of differentiation (Seyedin et al, 1981). There is a keen interest in gaining a greater understanding into the mechanism by which HMG-1 takes part or regulates these important activities.…”
mentioning
confidence: 99%